2012
DOI: 10.1186/1471-2474-13-159
|View full text |Cite
|
Sign up to set email alerts
|

The development of whole blood titanium levels after instrumented spinal fusion – Is there a correlation between the number of fused segments and titanium levels?

Abstract: BackgroundMost modern spinal implants contain titanium and remain in the patient’s body permanently. Local and systemic effects such as tissue necrosis, osteolysis and malignant cell transformation caused by implants have been described. Increasing tissue concentration and whole blood levels of ions are necessary before a disease caused by a contaminant develops. The aim of the present study was the measurement of whole blood titanium levels and the evaluation of a possible correlation between these changes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…They reported no statistically significant correlation between fused segments (r=-0.188, p=0.503), length of instrumentation (r=-0.329, p=0.231), number of interbody devices (r=-0.202, p=0.291), and increase of titanium levels over the observation period. They observed no statistically significant increase in titanium levels 12 months after surgery (mean difference=-7.2 μgL -1 , p=0.446) [25]. Those results are totally in contraposition with others in the literature and with ours too since not only do titanium levels not increase, but they decrease after surgery.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…They reported no statistically significant correlation between fused segments (r=-0.188, p=0.503), length of instrumentation (r=-0.329, p=0.231), number of interbody devices (r=-0.202, p=0.291), and increase of titanium levels over the observation period. They observed no statistically significant increase in titanium levels 12 months after surgery (mean difference=-7.2 μgL -1 , p=0.446) [25]. Those results are totally in contraposition with others in the literature and with ours too since not only do titanium levels not increase, but they decrease after surgery.…”
Section: Discussionsupporting
confidence: 62%
“…Metal liberation from metallic implants has been reported in the body fluids of patients carrying total hip or knee replacements, intramedullary nails, and, more recently, in patients undergoing instrumental spinal arthrodesis [2][3][11][12][14][15][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same authors also indicated that preterm birth, stillbirth, death, or toxicity symptoms were not seen when pregnant rats were given TiO 2 nanoparticles [ 15 ]. Ipach et al [ 16 ] investigated whether the number of screws and connectors used in spinal surgery had any correlation with blood titanium levels. They found no correlation between blood titanium levels and the number of titanium implants used for the surgery.…”
Section: Discussionmentioning
confidence: 99%